Regional Unemployment in the EU before and after the Global Crisis - Enrico P. Marelli; Roberto Patuelli; Marcello Signorelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
This article empirically assesses the evolution of European regions in terms of both employment and unemployment during the recent financial crisis and global recession. Our specific research questions are as follows: (i) has there been a reversal in employment and unemployment dynamics at a regional level during the crisis (2007–10) compared with the previous period (2004–07)? (ii) have the western regions ('old' EU states) behaved differently in response to the crisis compared with the eastern regions (NMS)? Finally, (iii) are the differences between the two groups of regions related to structural or institutional variables? After a review of the literature on the key determinants of regional unemployment, we summarise our main findings concerning the impact of the global crisis on the labour market. Our econometric investigation aims to answer the questions we pose. Structural characteristics are considered in terms of sector specialisation of regional economies. In addition, we consider certain institutional characteristics, by including indicators of the share of temporary workers and of long-term unemployed. Our analysis is then targeted at sub-samples of western and eastern European regions: we show that the critical factors for labour market performance during the crisis in these two groups differ greatly. From a methodological viewpoint, we exploit a spatial filtering technique which allowed us to greatly reduce any unobserved variable bias – a significant problem in cross-sectional models – by accounting for latent unobserved spatial patterns.
Keywords: C21; R12; 330